2021
DOI: 10.1021/acs.jpcc.1c04254
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively Understanding the Insights into CO2 Adsorption on Faujasite from the Heterogeneity and Occupancy Sequence of Adsorption Sites

Abstract: The heterogeneity in adsorption site is a fundamental characteristic of adsorption that is difficult to quantify. Herein, we quantify the site heterogeneity for CO 2 adsorption on NaX by recognizing the characteristics, types, and site occupancies at different loadings. We find an adsorption site geometry of Na••• OCO⊥ O z (where O z denotes an oxygen atom in the zeolite) and that the distance between C and O z is an indicator of heterogeneity. This distance is controlled by the interacting cations on SIII (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Unfortunately, Palomino et al did not provide any additional information to understand or predict the slope of the observed behavior of Q st with the Al/(Si + Al) ratio . Several theoretical works try to enhance the comprehension of the interactions of CO 2 and the framework where a specific adsorption site with an L-shape and T-shape configuration was observed [in an L-shape configuration, one CO 2 molecule is bridging one Na ion and the bridging oxygen atom (Oz) of the zeolite, whereas in the T-shape configuration, one CO 2 molecule is aligned between two adjacent Na + ions with the carbon atom of CO 2 placed over a bridging Oz atom of the framework at the vicinity of two adjacent windows; see Figure a for details]. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, Palomino et al did not provide any additional information to understand or predict the slope of the observed behavior of Q st with the Al/(Si + Al) ratio . Several theoretical works try to enhance the comprehension of the interactions of CO 2 and the framework where a specific adsorption site with an L-shape and T-shape configuration was observed [in an L-shape configuration, one CO 2 molecule is bridging one Na ion and the bridging oxygen atom (Oz) of the zeolite, whereas in the T-shape configuration, one CO 2 molecule is aligned between two adjacent Na + ions with the carbon atom of CO 2 placed over a bridging Oz atom of the framework at the vicinity of two adjacent windows; see Figure a for details]. ,, …”
Section: Resultsmentioning
confidence: 99%
“…134 Several theoretical works try to enhance the comprehension of the interactions of CO 2 and the framework where a specific adsorption site with an L-shape and T-shape configuration was observed [in an L-shape configuration, one CO 2 molecule is bridging one Na ion and the bridging oxygen atom (Oz) of the zeolite, whereas in the T-shape configuration, one CO 2 molecule is aligned between two adjacent Na + ions with the carbon atom of CO 2 placed over a bridging Oz atom of the framework at the vicinity of two adjacent windows; see Figure 6a for details]. 105,141,142 Our starting point is the experimental structure proposed by Pluth and Smith. 148 Since we are interested in the analysis of the role played by the surface electrostatic (due to the distribution of Na + ions) in the heat of adsorption, the calculation of the new descriptors requires the use of "reasonable" initial framework structures.…”
Section: Ml-based Models For Adsorption Propertiesmentioning
confidence: 99%
“…The Fourier transform infrared (FTIR) experiments were performed with self-supporting pellets activated in vacuum at 673 K. The FTIR spectra of CO 2 adsorbed on CaNaY(1) at ambient temperature and in the pressure range of 0–7 mbar are presented in panels A and C of Figure . In the ν 3 ( 12 CO 2 ) region (Figure A), a band at 2364 cm –1 is formed at low coverage and attributed to Ca 2+ ···OCO adducts. , Note that the highest frequency ν 3 band, observed after CO 2 adsorption on NaY, is at 2354 cm –1 . As the coverage increases, the band initially develops and then a complex feature is formed in the 2380–2330 cm –1 region.…”
mentioning
confidence: 99%
“…To design efficient adsorbents, it is necessary to ensure both high adsorption capacity and suitable binding energy. Various approaches are currently being used by the scientific community, , and cation-exchanged zeolites have attracted much attention as potential CO 2 adsorbents. An important feature of these materials is that, in many cases, large exchanged cations can simultaneously adsorb two or even three small molecules as CO and N 2 , thus providing a high adsorption capacity. In a recent study, we reported that, similar to CO and N 2 , two CO 2 molecules can be simultaneously bound to one Na + cation in NaY.…”
mentioning
confidence: 99%
See 1 more Smart Citation